Penerapan Asas Lex Fravo Reo Dalam Sistem Peradilan Pidana Di Indonesia - Muhamad Wahyu Andi Zulkipli (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This study discusses problems related to the application of the lex fravo reo principle in the criminal justice system in Indonesia which focuses on premeditated detention cases committed by former Kadif Propam Polri. Ferdy Sambo, S.H., S.I.K., M.H against his own aide Brigadier Nofriansyah Yosua at the National Police Service house. This study aims to find out why the principle of lex fravo reo is needed in the criminal justice system in Indonesia and how the principle of lex fravo reo differs in the old Criminal Code and in the new Criminal Code. In this study the author used a normative juridical approach. The results in this study show that the application of the lex favor reo principle is very important in the legal system and criminal justice system in Indonesia because it strives for justice to be given equally to defendants where if there is a change in the substance of the criminal law Then the provisions in favor of the defendant apply. The principle of lex favor reo in the old Criminal Code is actually as affirmed in Article 1 paragraph (2) of the old Criminal Code, which emphasizes that if there is a change in the substance of the criminal law, then what is applied is the rule that is most beneficial to the accused. Furthermore, in the new Criminal Code, the principle of lex favor reo is also formulated in Article 3 juncto Article 618 of the new Criminal Code, which in essence is not much different from the formulation of Article 1 paragraph (2) of the old Criminal Code.